Tasawuf, Nasionalisme, dan Gerakan Sosial: Studi Spiritualitas Transformasional Abah Sepuh dalam Konteks Kolonialisme dan Kemerdekaan (Jurnal Sosial Humaniora dan Pendidikan, 2023)
This study explores the role of the Sufi teachings of Sheikh Abdullah Mubarok bin Nur Muhammad (Abah Sepuh) through the Qadiriyah wa Naqsyabandiyah (TQN) Order of Suryalaya as a form of transformational spirituality in facing colonialism and building national awareness. With a historical-hermeneutic qualitative approach, this study examines the Tanbih text, the practice of tazkiyatun nafs, and the social structure of the pesantren community as an arena for peaceful yet strategic cultural resistance. The results of the study show that Sufi values ​​such as ikhlas, khidmah, sabar, and amanah not only shape pious individuals, but also communities that are empowered, independent, and have a national consciousness rooted in monotheism. The nationalism offered by Abah Sepuh rejects secularism and extremism, and instead unites love of the homeland with devotion to God. His teachings live as living texts in social practices, spiritual economy, and collective memory, making Sufism an ethical and social force that is relevant across time. This study is a development of the author's dissertation and academic book manuscript that is being prepared for publication, thus presenting theoretical and practical contributions to the study of Sufism and social development.